Catalytic Carbon Submicron Fabrication Using Home- Built Very-High Frequency Plasma Enhanced Chemical Vapour Deposition - Sukirno Sukirno; Satria Zulkarnaen Bisri; Rasih Yulia Sari; Lilik Hasanah; Mursal Mursal; Ida Usman; Darsikin Darsikin (Journal of Mathematical and Fundamental Sciences, 2008)
In this research, carbon nanotubes (CNT) fabrication has been tried by using an existing home-made Plasma Enhanced Chemical Vapour Deposition (PECVD) system. The fabrication is a catalytic growth process, whereby a Fecatalyst thin film is grown on the Silicon substrate by using dc-Unbalanced Magnetron Sputtering. Methane (CH4) as carbon source and diluted silane (SiH4) in hydrogen as hydrogen source (ratio 10:1) was used for the CNT fabrication with the Very High Frequency PECVD (VHF-PECVD) method. The fabrication process was executed at the relatively low temperature of 250oC, but with the higher operating plasma frequency of 70 MHz. Recently, a fabrication process with only a single gas source has been carried out as well, but using a modified VHF-PECVD system with an additional hot-wirecomponent. The attempt was done at an higher growth temperature of 400oC. Morphological characterizations, by using Scanning Electron Micrograph (SEM) and Scanning Probe Microscopy (SPM), and composition characterization, by using Energy Dispersion Analysis by X-Ray (EDAX), show convincing results that there are some signatures of CNT present.